Two dimensional array based overlay network for reducing delay of peer-to-peer live video streaming - Ibrahimy, Abdullah Faruq Ibn; Anwar, Farhat; Ibrahimy, Muhammad Ibn; Islam, Md. Rafiqul (2014)
Live video streaming is very useful for many events. For example, it can be very useful to make an announcement in an area, which is effected by natural disaster. So it is also very important to provide the live video stream without any time delay if possible. The live video data is streaming usually in a tree-based overlay network or in a mesh-based overlay network. In case of departure of a peer with additional upload bandwidth, the overlay network becomes very vulnerable to churn. In this paper, a two dimensional array-based overlay network is proposed for streaming the live video stream data. As there is always a peer or a live video streaming server to upload the live video stream data, so the overlay network is very stable and very robust to churn. Peers are placed according to their upload and download bandwidth, which enhances the balance of load and performance. The overlay network utilizes the additional upload bandwidth of peers to minimize chunk delivery delay and to maximize balance of load. The procedure, which is used for distributing the additional upload bandwidth of the peers, distributes the additional upload bandwidth to the heterogeneous strength peers in a fair treat distribution approach and to the homogeneous strength peers in a uniform distribution approach. The proposed overlay network has been simulated by QualNet from Scalable Network Technologies and results are presented in this paper. Both maximum delay and average delay has decreased compared to Fast-Mesh overlay network. The percentage change in both of maximum and average delay time are below 30%, even though the number of nodes increases 10 times.